A randomised trial of granulocyte-macrophage colony-stimulating factor for neonatal sepsis: childhood outcomes at 5 years. Issue 4 (28th April 2015) - Marlow, Neil; Morris, Timothy; Brocklehurst, Peter; Carr, Robert; Cowan, Frances; Patel, Nishma; Petrou, Stavros; Redshaw, Margaret; Modi, Neena; Doré, Caroline J
Abstract : Objective: We performed a randomised trial in very preterm, small for gestational age (SGA) babies to determine if prophylaxis with granulocyte macrophage colony stimulating factor (GM-CSF) improves outcomes (the PROGRAMS trial). GM-CSF was associated with improved neonatal neutrophil counts, but no change in other neonatal or 2-year outcomes. As subtle benefits in outcome may not be ascertainable until school age we performed an outcome study at 5 years. Patients and methods: 280 babies born at 31 weeks of gestation or less and SGA were entered into the trial. Outcomes were assessed at 5 years to determine neurodevelopmental and general health status and educational attainment. Results: We found no significant differences in cognitive, general health or educational outcomes between 83 of 106 (78%) surviving children in the GM-CSF arm compared with 81 of 110 (74%) in the control arm. Mean mental processing composite (equivalent to IQ) at 5 years were 94 (SD 16) compared with 95 (SD 15), respectively (difference in means −1 (95%CI −6 to 4), and similar proportions were in receipt of special educational needs support (41% vs 35%; risk ratio 1.2 (95% CI 0.8 to 1.9)). Performance on Kaufmann-ABC subscales and components of NEPSY were similar. The suggestion of worse respiratory outcomes in the GM-CSF group at 2 years was replicated at 5 years. Conclusions: The administration of GM-CSF to very preterm SGA babies is not associated with improved or more adverse neurodevelopmental, general health or educational outcomes at 5 years. Trial registration number: ISRCTN42553489.